Hypoxic high-intensity interval exercise alters heart rate variability and substrate oxidation during recovery - Lubben, K.; Blair, J.; Adeboye, A.; Kelly, L.; Basset, F. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: The beat-by-beat change in heart rate, the so-called heart rate variability (HRV), is dependent on the cross-talk between sympathetic and parasympathetic nervous systems (SNS and PNS) (Yamamoto et al., 1996). HRV is affected by several factors such as exercise intensity, training status, health condition, gender, and environmental conditions, to name a few (Darr et al., 1988). However, no study has examined the cumulative effect of exercise and hypoxia on the sympathovagal balance and its potential association with the change in substrate partitioning during recovery. The purpose of this study was, therefore, to examine the effect of hypoxic exercise on HRV, and its association with change in substrate oxidation. METHODS: Eight active healthy males (age: 31±11 years; height: 180±7 cm; weight: 83±8 kg; BMI: 25±1 kg•m-2; V O2max: 4.4±0.6 L/min) were subjected to a 45-minute high-intensity interval (HII) cycling protocol in normoxia (FiO2= 0.2093) and hypoxia (FiO2= 0.15), respectively. In addition, a basal metabolic rate (BMR) and three 30-minute postexercise metabolic rates over a 3-hour period were recorded in normoxia. Maximal oxygen uptake and peak power output were determned using a ramp cycling test in normoxia. HII consisted of alternating 3 minutes at 70% and 3 minutes at 35% PPO in both conditions. ECG, RPE, and blood lactate were recorded during exercise while substrates oxidation was measured pre- and post-exercise along with ECG and blood lactate. RESULTS: During exercise, RPE was higher (p<0.01) and lactate increased (p=0.001) at each point of time in hypoxia, with no change in normoxia. After hypoxic exercise, SNS/PNS ratio was significantly higher (p<0.01) and significantly decreased through time in both conditions (p<0.01). In addition, a significant interaction between time and conditions (p<0.02) showed a decrease in lactate concentration through time post-hypoxic exercise. DISCUSSION: The findings showed that a single bout of hypoxic exercise alters the autonomic nervous system activity post-exercise along with shifting substrate partitioning from glycolytic to lipolytic energy production. The significant decrease in blood lactate concentration post-hypoxic exercise supports the notion that hypoxic HII induces a greater muscle glycogen depletion leading to increased fat oxidation to sustain glycogenesis and gluconeogenesis to maintain blood glucose level during recovery.